2023
DOI: 10.1002/adfm.202300547
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic Transition Metal Nitride Electrode Promotes Nucleophile Oxidation Reaction for Practicable Hybrid Water Electrocatalysis

Abstract: Glycerol electrooxidation (GOR), as a typical nucleophile oxidation reaction, is deemed as a promising alternative anodic route to assist cathodic hydrogen evolution reaction. However, the investigations of high-performance catalysts and industrial-scale application of GOR remain a grand challenge. Herein, biphasic Ni 3 N/Co 3 N heterostructure nanowires (denoted as Ni 3 N/ Co 3 N-NWs) are proposed as an efficient bifunctional catalyst, which realizes a high Faradaic efficiency of 94.6% toward formate producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…It is reported that the electronic structure of the active sites can affect the charge transfer property of the catalysts to optimize the adsorption/desorption of reactants and products, accompanied by accelerating reaction kinetics, thus facilitating catalytic efficiency . In recent years, various strategies, such as interface engineering, defect engineering, and heteroatom doping, have been used to tune the electron configuration of catalysts to enhance the catalytic activity. Combining suitable components with different energy structures to construct heterogeneous catalysts could generate an internal electric field and induce the formation of oppositely charged regions, , thus facilitating proton transport and local charge density redistribution at the heterointerface. In addition, the introduction of sulfur vacancies could change the electronic structure of adjacent metal atoms due to the different electronegativity, resulting in the adjacent metal active sites losing electrons, which could optimize the adsorption of reaction intermediates .…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the electronic structure of the active sites can affect the charge transfer property of the catalysts to optimize the adsorption/desorption of reactants and products, accompanied by accelerating reaction kinetics, thus facilitating catalytic efficiency . In recent years, various strategies, such as interface engineering, defect engineering, and heteroatom doping, have been used to tune the electron configuration of catalysts to enhance the catalytic activity. Combining suitable components with different energy structures to construct heterogeneous catalysts could generate an internal electric field and induce the formation of oppositely charged regions, , thus facilitating proton transport and local charge density redistribution at the heterointerface. In addition, the introduction of sulfur vacancies could change the electronic structure of adjacent metal atoms due to the different electronegativity, resulting in the adjacent metal active sites losing electrons, which could optimize the adsorption of reaction intermediates .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Zhang et al reported a biphasic transition metal nitride electrode by in situ growing Ni 3 N/Co 3 N heterostructure nanowires with abundant heterointerfaces on Ni foam. 34 This electrode exhibited remarkable activity for nucleophilic reaction electrocatalysis, achieving an ultrasmall work potential of 1.26 V to reach a current density of 50 mA cm −2 for the GOR and an excellent FE of 94.6% for formate production. Importantly, under a two-electrode configuration, the electrode enabled the concurrent production of formate and H 2 , delivering current densities of 50 and 400 mA cm −2 at 1.47 and 2.04 V, respectively, which surpass those required forthe OWS for O 2 and H 2 generation (1.72 and 2.22 V at 50 and 400 mA cm −2 , respectively).…”
Section: Organic Upgrading-assisted H2 Productionmentioning
confidence: 99%
“…7,15 Data for the above two critical performance indicators of the electrolyzer were obtained from the literature (Fig. 8c), 15,110,130,148,151,191,192,237–251 from the widely studied systems including methanol, 11 and glycerol oxidation. In most reports, the E E of the AAC-incorporated electrolyzer is 20% lower than that of the alkaline water electrolyzer, but the R P is much lower due to the limited current density.…”
Section: Techno-economic Considerations On the Alternative Anodic Che...mentioning
confidence: 99%